Kinetics of bovine cryopreserved sperm cells after sexing by fl ow cytometry - Carvalho, José de Oliveira; Sartori, Roberto; Lemes, Amanda Prudêncio; Mourão, Gerson Barreto; Dode, Margot Alves Nunes (Pesquisa Agropecuaria Brasileira, 2010)
The objective of this study was to compare the kinetics of bovine cryopreserved nonsexed, sexed for X and sexed for Y sperm cells before and after selection using Percoll gradient. Cryopreserved nonsexed (NS group) semen samples and sexed for X (SX group) and for Y (SY group) by flow cytometry, from four different sires, were analyzed for motility by computer-assisted semen analysis (CASA), and the remainder of the sperm samples for each group was submitted to Percoll (45:60%) gradient selection. After Percoll selection, the same sperm analyses done before the passing through Percoll gradient were performed. Sperm motility was higher in the NS group than in the SX and SY groups, and no differences were observed between these last two groups for any of the sperm parameters evaluated by CASA, either before or after Percoll selection. Percoll increased motility for all groups. Changes in other characteristics evaluated by CASA were observed only in the NS group. Sex-sorting procedure by flow cytometry affected sperm kinetics, and Percoll gradient selection increases motility in sexed and nonsexed sperm without affecting the kinetics of nonsexed sperm.
Keywords: Percoll gradient; sperm motility; sexed sperm